Independent Immigrant Selection Criteria and Equality Rights : Discretion, Discrimination and Due Process - Dobson-Mack, Anne (Les Cahiers de droit, 1993)
This article is a response to Walter Chi Yan Tom's « Equality Rights in the Federal Independent Immigrant Selection Criteria », published in 1990 in this journal, in which it is asserted that the federal independent immigrant selection criteria are discriminatory within the meaning ofs. 15 of the Charter and are not demonstrably justified according to s. 1.The author argues that Tom badly distorts the section 15 meaning of discrimination when he equates the discretion and drawing of distinctions, which are part of the administrative decision-making process by which independent immigrants are selected, with section 15 discrimination. The article also addresses the conflict between State sovereignty and the sovereignty of universal legal principles, a conflict which is raised in Tom's article. Finally, the author examines the ways in which standing rights have been used by the courts in immigration decisions to avoid dealing with substantive Charter issues, and criticizes the lack of rationality and coherence in the assignment of due process rights to different classes of nonnationals under current immigration law.